Effect of different concentration of cellulose nanocrystals comprising hydroxyethyl cellulose/poly (vinyl alcohol) as a bone tissue engineering scaffold - Farah Hanani, Zulkifli; Nor Sarahtul Nadirah, Hairol Nizan (Trans Tech Publications Ltd, Switzerland, 2020)
In this study, biodegradable scaffolds based on hydroxyethyl cellulose (HEC) (5 wt%) and poly (vinyl alcohol) (PVA) (15 wt%) with different percentages of celullose nanocrystal (CNC)(1 and 7 wt%) were fabricated by lyophilization method to get highly porous scaffolds. These scaffolds were made water insoluble by cross-linking via heat treatment. The morphology and thermal properties of HEC/PVA/CNCs scaffolds were characterized by using Scanning Electron Microscope (SEM) and Thermogravimetric Analysis (TGA). The morphological study showed thatboth prepared scaffold have highly porous structures with good pore interconnected structure. It was observed that thermal properties of scaffolds increased significantly as the concentration of CNCs increased. Cytotoxicity studies on scaffolds were carried out by utilizing human fetal osteoblast (hFOB) cells using DAPI nuclear stain and then confirmed using SEM. hFOB cells were able to attach and spread on all scaffolds. Incorporated CNCs as reinforcing nanofiller on scaffolds promising a superior functionality in bone tissue engineering.